Biopolitical Reflection on Human Safety: Ukrainian and Belarus Experience - Kravets, Anastasia (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2021)
Biopolitical reflection is seen as a way of understanding the specifics of being “bios politicos.” It’s means as the understanding the transformational processes in bios and involve the appropriate political reaction, and internal changes “bios politicos,” its self-realization as a subject and object of policy, able to initiate profound transformations of politics and power in biopolitics and biopower. The concept of “bios politicos,” his life, freedom and safety are in the focus of scientific analysis. The key question: сan “bios politicos” exist and function effectively in conditions of danger, in conditions where every word, every action that is unacceptable to the disciplinary authorities can lead to punishment or even death? The aim is to prove that politics and power in the 21st century in Europe cannot and should not exist in a disciplinary form. Their transformation is possible due to the activity of a person as a conscious subject of social and political activity. The complex nature of the scientific problem involves the use of appropriate methods that combine different types of systems analyses: system-structural analysis, system-functional, system-historical analysis, as well as the method of rational reconstruction and prognostic method. The key hypothesis is that today Ukraine is very close (or seeks to get closer) to the implementation of the concepts of biopolitics and biopower. 2014 is certainly an illustration of the “bios politicos” resistance to disciplinary action, despite disciplinary techniques, including the threat of death. Belarusian society, after the 2020 presidential election, has shown such a high level of consolidation and awareness, non-acceptance of disciplinary techniques in the form of threats, violence, and punishment, that we can assume the beginning of transformational change. It is biopolitics and biopower today that is the response of the conscious subject – “bios politicos” to the crisis of disciplinary power, its techniques of domination, control, and violence. Biopolitics and biopower allow “bios politicos” to exist and develop freely in their country, to realize their knowledge and aspirations, to be realized in all spheres of life knowing that the main task of the state is to protect his life and freedom.

Refleksja biopolityczna jest postrzegana jako sposób na zrozumienie specyfiki bycia „bios politikos.” Oznacza to rozumienie procesów transformacyjnych w „bios” i pociągających za sobą odpowiednią reakcję polityczną oraz zmiany wewnętrzne „bios politikos”, jego samorealizację jako podmiotu i przedmiotu polityki, zdolnego do inicjowania głębokich przemian politycznych i władzy w biopolityce i biowładzy. Pojęcie „bios politikos”, jego życie, wolność i bezpieczeństwo znajdują się w centrum analizy naukowej. Kluczowe pytanie: czy „bios politikos” może istnieć i funkcjonować skutecznie w warunkach zagrożenia, w warunkach, w których każde słowo, każde działanie nieakceptowane przez władze dyscyplinarne może prowadzić do kary, a nawet śmierci? Celem jest udowodnienie, że polityka i władza w XXI wieku w Europie nie mogą i nie powinny istnieć w formie dyscyplinarnej. Ich przemiana jest możliwa dzięki aktywności człowieka jako świadomego podmiotu działalności społecznej i politycznej. Złożoność problemu naukowego wiąże się z zastosowaniem odpowiednich metod łączących różne rodzaje analiz systemowych: analizę systemowo-strukturalną, systemowo-funkcjonalną, systemowo-historyczną, a także metodę racjonalnej rekonstrukcji i metodę prognostyczną. Kluczową hipotezą jest to, że dziś Ukraina jest bardzo bliska (lub dąży do zbliżenia) realizacji koncepcji biopolityki i biowładzy. Rok 2014 jest z pewnością ilustracją oporu „bios politikos” wobec działań dyscyplinarnych, pomimo stosowanych technik dyscyplinarnych, w tym groźby śmierci. Społeczeństwo białoruskie po wyborach prezydenckich w 2020 r. wykazało tak wysoki poziom konsolidacji i świadomości, nieakceptowania technik dyscyplinarnych w postaci gróźb, przemocy i kar, że możemy założyć początek transformacji transformacyjnej. To biopolityka i biowładza są dziś odpowiedzią świadomego podmiotu – „bios politikos” na kryzys władzy dyscyplinarnej, jej techniki dominacji, kontroli i przemocy. Biopolityka i biowładza pozwalają „bios politikos” swobodnie istnieć i rozwijać się w swoim kraju, realizować swoją wiedzę i aspiracje, realizować się we wszystkich sferach życia, wiedząc, że głównym zadaniem państwa jest ochrona jego życia i wolności.
Biopolityczna refleksja bezpieczeństwa człowieka: doświadczenia ukraińskie i białoruskie
Keywords: bios; bios politicos; biopolitics; biopower; life; human safety; resistance; freedom; transformation; bios; bios politikos; biopolityka; biowładza; życie; bezpieczeństwo człowieka; opór; wolność; transformacja